Effect of Ionic Size on Equilibrium Constant of Some Uni-Bivalent Ion Exchange reactions - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
Ion exchange resins in chloride and iodide form were equilibriated with oxalate ion solution of seven different concentrations from 0.010 M to 0.050 M, in temperature range of 30 to 45°C. The difference in the ionic size of exchangeable CI- and I- ions on the resin results in variation of equilibrium constant (K) values, i.e., for Cl-/C2O42- exchange value of K at 30°C was calculated to be 19.5, while for I-/C2O42- exchange the value of K was calculated to be 0.260 for same temperature. For both uni-bivalent exchanges the equilibrium constant (K) values increases with increase in temperature, indicating the endothermic ion exchange reaction having enthalpy of 12.2 kJ/mole for Cl-/C2O42- exchange and 14.5 kJ/mole for I-/C2O42- exchange.